Odpowiedzi

2009-12-06T21:07:00+01:00
Wszystkie przyklady korzystają ze wzorów:
log a*b = log a + log b
log a/b = log a - log b



1) log z7 4=a i log z7 3=b oblicz logz7 36
log z7 36 = log z7 (4*3*3) = log z7 4 + log z7 3 + log z7 3 = a+b+b

2) logz4 3=a logz4 5=b oblicz logz4 1,8
log z4 1,8 = log z4 9/5 = log z4 (3*3/5) = log z4 3 + log z4 3 - log z4 5 = a+a-b

3) logz5 4=a logz5 27=b oblicz logz5 6
log z5 6 = 1/6 * 6 * log z5 6 =
= 1/6 (log z5 6 + log z5 6 + log z5 6 + log z5 6 + log z5 6 + log z5 6) =
= 1/6 * log z5 (6*6*6*6*6*6) =
= 1/6 * log z5 (2*3*2*3*2*3*2*3*2*3*2*3) =
= 1/6 * log z5 (2*2*2*2*2*2*3*3*3*3*3*3) =
= 1/6 * log z5 (4*4*4*27*27) =
= 1/6 * (log z5 4 + log z5 4 + log z5 4 + log z5 27 + log z5 27) =
= 1/6 * (3a+2b) = 1/2 a + 1/3 b
4 3 4